Development of Zakat Collection During Caliph Umar al-Khattab - Abdul Hamid, Hamizul bin; Abdul Hamid, Ahmad Faisal; Abdul Wahab, Adibah (Journal Al-Muqaddimah, 2019)
Discussion about great figure will always touch on the contribution they made. It's including Umar al-Khattab. He is not just an ordinary figure, because in the era of his leadership, many great innovations apply. It is including the innovation of zakat. He introduced many innovations, especially in zakat's collection matter. This article will discuss two things, (1) Innovations that have been carried out by Umar al-Khattab in the field of zakat collection, (2) The role of attitude of Umar al-Khattab that influenced the innovation. To achieve this objective, the researcher applies the fully qualitative method by referring to books or related material. The results found that Umar al-Khattab had succeeded introducing 14 innovations in zakat's collection. It's also proved that Umar al-Khattab's attitude is deeply influences him in his innovation. However, there are still many more innovations in managing zakat which need to be discussed further in future writing.